Development of an Immune-Related LncRNA Prognostic Signature for Glioma - Cao, Yudong; Zhu, Hecheng; Tan, Jun; Yin, Wen; Zhou, Quanwei; Xin, Zhaoqi; Wu, Zhaoping; Jiang, Zhipeng; Guo, Youwei; Kuang, Yirui; Li, Can; Zhao, Ming; et al. (Frontiers in Genetics, 2021)
Introduction: Glioma is the most common primary cancer of the central nervous system with dismal prognosis. Long non-coding RNAs (lncRNAs) have been discovered to play key roles in tumorigenesis in various cancers, including glioma. Due to the relevance between immune infiltrating and clinical outcome of glioma, identifying immune-related lncRNAs is urgent for better personalized management. Materials and methods: Single-sample gene set enrichment analysis (ssGSEA) was applied to estimate immune infiltration and glioma samples were divided into high immune cell infiltration group and low immune cell infiltration group. After screening differentially expressed lncRNAs in two immune groups, least absolute shrinkage and selection operator (LASSO) Cox regression analysis was performed to construct an immune-related prognostic signature. Additionally, we explored the correlation between immune infiltration and the prognostic signature. Results: A total of 653 samples were appropriate for further analyses and 10 lncRNAs were identified as immune-related lncRNAs in glioma. After univariate Cox regression and LASSO Cox regression analysis, 6 lncRNAs were identified to construct a prognostic signature for glioma which could be taken as independent prognostic factors in both univariate and multivariate Cox regression analyses. Moreover, risk score was significantly correlated with all the 29 immune-related checkpoints expression (p < 0.05) in ssGSEA except neutrophils (p = 0.43). Conclusion: The study constructed an immune-related prognostic signature for glioma, which contributed to improve clinical outcome prediction and guide immunotherapy.